(untitled) (Research, Society and Development, 2025)
Surgical site infections (SSI) are common complications in colorectal surgeries, increasing morbidity and hospital costs. Surgical antibiotic prophylaxis (SAP) is an essential measure to prevent these infections, with its effectiveness depending on the choice of antibiotic, timing of administration, and adherence to protocols. This study, an integrative literature review, analyzed the effectiveness of the main antibiotics used in SSI prophylaxis in colorectal surgeries. Eight articles published between 2020 and 2024 were selected from the PubMed, SciELO, and Google Scholar databases using specific descriptors. The results indicated that the combination of oral and intravenous prophylaxis, particularly with nitroimidazoles (ornidazole, metronidazole), aminoglycosides (neomycin), macrolides (erythromycin), and cephalosporins (cefoxitin, ceftriaxone), significantly reduced SSI rates, especially in colon surgeries. However, prolonged prophylaxis did not show additional benefits and may delay postoperative recovery. The implementation of multifaceted preventive protocols, such as bundles, proved effective in reducing SSI, but adherence to preventive measures and monitoring of antimicrobial resistance are crucial. It is concluded that antibiotic prophylaxis is an essential strategy in preventing SSI in colorectal surgeries and should be personalized according to patient and procedural characteristics, ensuring a balance between efficacy and safety.